Landscapes and Landforms of the Central Sahara - Knight, Jasper; Merlo, Stefania; Zerboni, Andrea (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book describes the Central Sahara region, bringing together an unprecedented combination of diverse and often historic research published in different languages in order to describe its varied landscapes and landforms. The Central Sahara region consists of Libya, Algeria, Mali, Niger and Chad, countries that share similar landscape histories and common landscape traits, including massifs, sand seas, paleowater features and large depressions. Furthermore, human settlement of this region goes hand-in-hand with climate and environmental changes and landscape evolution during the Holocene and earlier; hence, Central Saharan landscapes and landforms provide valuable insights into landscape-human relationships over long timescales. The book offers a comprehensive yet accessible reference source, drawing on both past and present interdisciplinary research and gathering the insights of authors from many different countries to explore a region that has largely been overlooked in available literature.
Part I. Background -- Geology, climate and landscape evolution -- Quaternary and holocene palaeoclimates of the Sahara -- Plant and animal life in the Sahara -- Human exploitation of the Central Sahara -- Field investigation, remote sensing and geomorphological mapping -- Part II. Landforms and landscapes -- Evidence for past glaciations -- Volcanoes and igneous landforms -- Sandstone massifs -- Solutional landforms and karstic weathering -- Alluvial fans, escarpments, and pediments -- Hamada, serir, and desert pavement -- Sand seas - North -- Sand seas - South and west. .
Keywords: Physical geography; Earth sciences; Environment; Geography; Physical Geography; Earth Sciences; Environmental Sciences; Regional Geography